A Quantitative Relationship between Signal Detection in Attention and Approach/Avoidance Behavior - Viswanathan, Vijay; Sheppard, John P.; Kim, Byoung W.; Plantz, Christopher L.; Ying, Hao; Lee, Myung J.; Raman, Kalyan; Mulhern, Frank J.; Block, Martin P.; Calder, Bobby; Lee, Sang; Mortensen, Dale T.; et al. (Frontiers in Psychology, 2017)
This study examines how the domains of reward and attention, which are often studied as independent processes, in fact interact at a systems level. We operationalize divided attention with a continuous performance task and variables from signal detection theory (SDT), and reward/aversion with a keypress task measuring approach/avoidance in the framework of relative preference theory (RPT). Independent experiments with the same subjects showed a significant association between one SDT and two RPT variables, visualized as a three-dimensional structure. Holding one of these three variables constant, further showed a significant relationship between a loss aversion-like metric from the approach/avoidance task, and the response bias observed during the divided attention task. These results indicate that a more liberal response bias under signal detection (i.e., a higher tolerance for noise, resulting in a greater proportion of false alarms) is associated with higher “loss aversion”. Furthermore, our functional model suggests a mechanism for processing constraints with divided attention and reward/aversion. Together, our results argue for a systematic relationship between divided attention and reward/aversion processing in humans, and suggest that predictive inference can be achieved by combining experimental psychology with quantitative modeling.